Taxonomy of the Lessingianthus saltensis (Vernonieae, Asteraceae) species complex - Angulo, Maria Betiana (2012)
In this study, three species of Lessingianthus saltensis complex are described and illustrated, including two new species. The new taxa L. membranifolius and L. coriarius are diploid (2n = 2x = 32), while L. saltensis is tetraploid (2n = 4x = 64). Lessingianthus membranifolius is distinguished from the other taxa in the complex by the membranaceus leaves, phyllaries with a rounded apex and leaf blades basally obtuse with serrate margins. Lessingianthus coriarius can be easily separated from the other taxa of the group by the combination of coriaceus leaves, phyllaries apically acute and leaf blades acute at the apex, with entire margins. A lectotype is designated for L. saltensis.